Основные этапы развития позднемиоценовой фауны копытных и хоботных Северного Причерноморья - Короткевич, Е.Л. (Вестник зоологии, 1972)
Locations of the Hipparion genus fauna in the territory of the Ukrainian SSR south are sufficiently ordinary and numerous. On the basis of studying the species composition of the Late Miocene vertebrates one can outline definite stages in development of the North Black Sea area Hipparion fauna, specify geological age of the Meotic burials of the given region and biostratigraphic division of continental facies of these deposits.